1997
DOI: 10.1159/000190252
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Glomerulonephritis following Successive Inoculation of Five Different Serotypes of Group B Coxsackieviruses in Mice

Abstract: The purpose of the present investigation is to study renal injury by monthly viral inoculation into mice, using several different types of strains of enterovirus. A group of mice were inoculated intravenously with five different serotypes of group B coxsackieviruses (CB1 to CB5), once a month from 1 to 5 months of age and sacrificed monthly from 6 to 12 months of age. Mesangial proliferation and PAS-positive mesangial deposits in light microscopy and electron-dense deposits in electron microscopy were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…They have also been reported to be etiological agents in some renal diseases [7,8,9,10]. For example, experimental nephritis induced by CB4 was first described by Sun et al [11], and subsequent reports indicated relationships of CB4 with renal disease in humans [7,8] and experimental animals [12,13,14]. We recently demonstrated glomerular lesions with IgA deposits induced by intraperitoneal inoculations of CB4 in mice [13].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…They have also been reported to be etiological agents in some renal diseases [7,8,9,10]. For example, experimental nephritis induced by CB4 was first described by Sun et al [11], and subsequent reports indicated relationships of CB4 with renal disease in humans [7,8] and experimental animals [12,13,14]. We recently demonstrated glomerular lesions with IgA deposits induced by intraperitoneal inoculations of CB4 in mice [13].…”
Section: Introductionmentioning
confidence: 72%
“…By using pure cultures of human glomerular and tubular cells, Conaldi et al demonstrated that the infection of six CBs led to cytolysis in proximal tubular epithelial cells and glomerular podocytes [20]. Previously, we reported that CB4 caused pathological changes in experimentally infected mouse kidney [12,13,14]. We recently observed lesions similar to those of human IgA nephropathy in mice intravenously inoculated with CB4 once a month from 1 to 5 months of age, and we detected CB4 viral RNA in the mesangial lesions, using in situ hybridization [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these systems, genetic proclivity for altered systemic immunity is recognized and likely explains the predominance of IgAN [49][50][51]. However, in some instances, the known parameters of the immune response would not necessarily predict predilection for a strong IgA response or alterations in immunoregulation; nonetheless, strong serum IgA responses and IgA predominance or co-dominance in a subsequent glomerulonephritis is observed [68][69][70][71][72]. The antigens in these systems are bacterial or viral pathogens that might invoke innate immunity, which modulates the adaptive antibody response through mechanisms that are currently being elucidated (see 'T Cell Regulation and Cytokine Polarity' , below).…”
Section: Generation Of Iga By Extramucosal (Systemic) Immunizationmentioning
confidence: 99%
“…Indeed, co-stimulation with 'superantigen' , vaccination of selected strains of rodents predisposed towards an immune response favoring IgA production and/or Th2 cytokine profiles, or immunomodulation by innate responses can also lead to IgAN [33,36,[49][50][51][68][69][70][71][72]. In addition, very intense cognate responses can drive immune responses with specificity for elements that are not a component of the intense stimulus, which is especially true for simpler antigens, those that resemble commensals or pathogens, or those that are prevalent in the environment in which the host survives.…”
Section: Polyclonal Activation and Dysregulated Ig Productionmentioning
confidence: 99%